The Influence of the Digital Generation in the Development of Farming Communities - Fitri Yani (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2022)
Many people agree that rural development is facilitated by the inclusion of digital technologies into agriculture. Still, the influence of the digital generation young people raised with digital tools and platforms in determining this change is yet mostly unknown. With an eye towards how they mediate technological adoption, support innovation, and negotiate intergenerational relations, this study critically investigates how the digital generation shapes the evolution of farming communities. Using a critical literature review approach, the study synthesises results from 87 peer-reviewed publications, policy studies, and scholarly publications covering the domains of agricultural development, digital innovation, and rural sociology. Four main themes emerge from the study: (1) the digital generation as intermediaries in knowledge transfer and digital literacy; (2) their role in driving agri-tech entrepreneurship; (3) the negotiation of intergenerational relationships in the context of technological change; and (4) ongoing structural barriers to digital inclusion, especially in rural and gendered contexts. These results underline the possible agents of change of the digital generation as well as the socioeconomic and infrastructure limitations that restrict their influence. Through emphasising generational agency, the study helps to provide a more complex knowledge of digital revolution in agriculture. It advocates governmental changes supporting young-led innovation, generational cooperation, and systematic inequality in access to digital resources.